Evaluation of Malaysian' s children websites using fuzzy computing with expressions - Mahmud, Murni; Md. Tap, Abu Osman; Raja Mohd., Noorhazwani (2010)
Children have difficulty in understanding numbers unlike adults. They are easily attracted to displayed images and icons rather than numbers. Therefore, in any evaluation with children, it is better to avoid the use of numerical scaling towards them. For this study is concern on the method used when evaluating with children, this study promotes the use of linguistic expressions as a method in the evaluation process. Linguistic expressions are applicable to children where expressions are much likeable by children than numerical scaling. Evaluation of the linguistic expression is applied during the interviews, questions and answers session with the children. The children websites was chosen in the evaluation because websites technology has becoming more permeable towards children nowadays. Websites are important to children as a medium to provide education learning and entertainment. Despite that, children websites in Malaysia seems to be limited. It is rare enough to find Malaysian based websites for children in the search engine. Hence, this study investigates the current status of Malaysian's children website and their design and content characteristics as well as proposing the method of fuzzy computing with expressions in the evaluation process. In the near future, this study perhaps will initiate Malaysian websites developer to create more children websites in this country.